2004
DOI: 10.1021/ol036287x
|View full text |Cite
|
Sign up to set email alerts
|

p-(1H-Phenanthro[9,10-d]imidazol-2-yl)- Substituted Calix[4]arene, a Deep Cavity for Guest Inclusion

Abstract: The reaction of tetra-p-formyltetra-O-propylcalix[4]arene with phenanthrenequinone in the presence of NH(4)OAc affords compound 2, a new class of calixarene with an expanded aromatic cavity, that could be stabilized by hydrogen-bonded bridges and/or ion pairing, thus preventing collapse into fully stacked pinched cone conformations as depicted. Two partially protonated calixarenes interdigitate in the solid state to give rise to a self-assembled face-to-face dimer, stabilized by pi-pi stacking interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Mendoza et al [93] synthesized an extended calix[4]arene 26 having the wide, coplanar 1 H -phenanthro[9,10-d]imidazol-2-yl aromatic surface situated at the upper rim. They demonstrated that an expanded cavity of 26 could be created by hydrogen-bonded bridges or ion pairing.…”
Section: Molecular Recognition Based Upon Extended Calix[4]arenesmentioning
confidence: 99%
“…Mendoza et al [93] synthesized an extended calix[4]arene 26 having the wide, coplanar 1 H -phenanthro[9,10-d]imidazol-2-yl aromatic surface situated at the upper rim. They demonstrated that an expanded cavity of 26 could be created by hydrogen-bonded bridges or ion pairing.…”
Section: Molecular Recognition Based Upon Extended Calix[4]arenesmentioning
confidence: 99%
“…11,12 Alternatively, the reactions of 1,2-diketone with aldehyde and ammonium acetate have been carried out by Lewis acid catalysis under relatively mild conditions. 13,14 Here we report the development of a new CMC-supported lanthanide catalyst and its application to the synthesis of substituted imidazoles via the reaction of 1,2-diketone with aldehyde and ammonium acetate under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[8] It was shown that the overall conical shape of 2 can be partially stabilized by ion-paired bridges between the vicinal imidazole moieties (such as 2·TFA 4 ), which prevent full collapse of the cavity (Scheme 1). [8] The use of a 3,8-phenanthroline instead of the phenanthrene moiety locates the heteroatoms at the corners of a square with the 908 angles required for bridging with metal ions with a preference for square planar or octahedral coordination. [9] We selected {Re(CO) 3 Br} as the metal bridges since highly stable tetranuclear square boxes based on porphyrins have been reported for this metal core.…”
mentioning
confidence: 99%
“…[10] The expanded 3,8-phenanthrolinoimidazolylcalix [4]arene (1) was obtained in 62 % yield by reaction of tetra-O-octyl para-formylcalix [4]arene (6) [11] with eight equivalents of 3,8-phenanthroline-5,6-dione (5) in the presence of an excess of ammonium acetate in refluxing acetic acid (Scheme 2). [8] The hitherto unknown quinone 5 was obtained in moderate yield by cyclization of bisimine 3 under strongly acidic conditions followed by oxidation of the resulting 2,7-diazaphenanthrene (4) [12] under similar conditions as those reported for 1,10- phenanthroline. [13] Finally, the metallobridged cavitand 1·Re 4 was formed in 80 % yield from reaction of 1 with four equivalents of [Re(CO) 5 Br] in refluxing tetrahydrofuran (THF).…”
mentioning
confidence: 99%